Analisis Pola Kemitraan Peternak Ayam Broiler dengan PT. Mitra Sinar Jaya di Kabupaten Tabanan - YULIARI, DEWA AYU PUTRI; SUAMBA, I KETUT; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Analysis of Partnership Pattern of Broiler Farmers and PT. Mitra Sinar Jaya in Tabanan Regency Livestock production is a potential agricultural sub sector. Broiler chicken is among livestock commodities that have increased in production and have the potential to be developed. The development of the agricultural sub-sector in Tabanan Regency can be seen from the high number of broiler chicken farmers in Tabanan Regency. However, broiler chicken farming in Tabanan Regency still faces a variety of problems such as limited capital, quality of production and production costs. The purpose of this study is to determine the existing partnership pattern between broiler farmers and PT. Mitra Sinar Jaya in Tabanan Regency and the income of broiler farmers in partnership with PT. Mitra Sinar Jaya. The result shows that the existing partnership pattern is in the form of plasma core partnership, in which PT. Mitra Sinar Jaya acts as the nucleus and partner farmers act as the plasma. Income of broiler farmers in partnership with PT. Mitra Sinar Jaya is not profitable. This is indicated by the value of the R / C Ratio which is smaller than 1. The strategy that needs to be done by PT. Mitra Sinar Jaya is to make regulations and guidance regarding production that can ensure the sustainability of the business of broiler farmers and the partner company.